2014
DOI: 10.1371/journal.pone.0092227
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 Signaling Preserves Microvascular Integrity and Renal Function in Chronic Kidney Disease

Abstract: The progressive decline of renal function in chronic kidney disease (CKD) is characterized by both disruption of the microvascular architecture and the accumulation of fibrotic matrix. One angiogenic pathway recently identified as playing an essential role in renal vascular development is the stromal cell-derived factor-1α (SDF-1)/CXCR4 pathway. Because similar developmental processes may be recapitulated in the disease setting, we hypothesized that the SDF-1/CXCR4 system would regulate microvascular health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…In contrast, a role for the SDF‐1‐CXCR4/CXCR7 signalling pathways is supported by converging lines of evidence: (i) a strong expression of CXCR4 and CXCR7 by our podocytes; (ii) the constitutive production of SDF‐1α; (iii) activation of the cognate intracellular signalling molecules (ERK1/2) after a relatively short‐term exposure to linagliptin; (iv) the effects exerted by AMD3100 alone; and (v) the synergistic interaction between AMD3100 and linagliptin. Thus, our data corroborate previous findings on the expression of DPP4 by podocytes, the role played by DPP4 in SDF‐1 proteolytic processing (SDF‐1 being one of the best DPP4 substrates) and the expression of SDF‐1 peptides and their receptors by podocytes (Lambeir et al ., ; De La Luz Sierra et al ., ; Mazzinghi et al ., ; Stokman et al ., ; Chen et al ., ). More importantly, these observations allow us to propose a linkage between renal effects of gliptins resulting from the inhibition of the glomerular DPP4 and interference with the SDF‐1‐CXCR4/CXCR7 pathways.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, a role for the SDF‐1‐CXCR4/CXCR7 signalling pathways is supported by converging lines of evidence: (i) a strong expression of CXCR4 and CXCR7 by our podocytes; (ii) the constitutive production of SDF‐1α; (iii) activation of the cognate intracellular signalling molecules (ERK1/2) after a relatively short‐term exposure to linagliptin; (iv) the effects exerted by AMD3100 alone; and (v) the synergistic interaction between AMD3100 and linagliptin. Thus, our data corroborate previous findings on the expression of DPP4 by podocytes, the role played by DPP4 in SDF‐1 proteolytic processing (SDF‐1 being one of the best DPP4 substrates) and the expression of SDF‐1 peptides and their receptors by podocytes (Lambeir et al ., ; De La Luz Sierra et al ., ; Mazzinghi et al ., ; Stokman et al ., ; Chen et al ., ). More importantly, these observations allow us to propose a linkage between renal effects of gliptins resulting from the inhibition of the glomerular DPP4 and interference with the SDF‐1‐CXCR4/CXCR7 pathways.…”
Section: Discussionmentioning
confidence: 97%
“…Until now, conflicting results have been reported on the role of the SDF-1-CXCR4/CXCR7 pathways in the kidney. Indeed, some studies have suggested a beneficial function for SDF-1 (Mazzinghi et al, 2008;Stokman et al, 2010;Chen et al, 2014;Nistala et al, 2014). In contrast, it has also been shown that a CXCR4-mediated podocyte proliferation could contribute to the development of certain glomerular diseases (Ding et al, 2006;Rizzo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a slightly damaged kidney, the CXCR4/SDF-1 signal facilitates the repair effect of CD34-positive stem cells and preserves microvascular integrity. 12 In allografts with severe ischemia/reperfusion-induced injury, the high expression of CXCR4/SDF-1 axis can overcome the repair effect and accelerate the chronic inflammatory process by chemoattracting mononuclear cells. 13 This finding also explains the discrepancy in the role of the CXCR4/SDF-1 pathway in the ischemic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…13 This finding also explains the discrepancy in the role of the CXCR4/SDF-1 pathway in the ischemic kidney. Chen and associates showed that augmentation of this pathway attenuated the progression of chronic renal disease in a rat nephrectomy model, 12 whereas Gao and associates proved that down-regulated expression of SDF-1 provided a protective effect of allografts in a renal transplant model. 10 As we have demonstrated, the CXCR4/SDF-1 axis is up-regulated in allografts, leading to renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%